Active edible coating effectiveness in shelf-life enhancement of trout (Oncorhynchusmykiss) fillets. Issue 1 (January 2015) - Volpe, M.G.; Siano, F.; Paolucci, M.; Sacco, A.; Sorrentino, A.; Malinconico, M.; Varricchio, E.
Abstract Carrageenan-based biocomposites have significant potential to develop packaging films and coatings for shelf-life extension of food products. In this study trout fresh fillets were separated into three groups: uncoated trout fillet (UTF), coated with carrageenan-based materials (coated trout fillet, CTF), and coated with carrageenan-based materials containing 1 g/100 mL essential lemon oil (active coated trout fillet, ACTF). The effect of carrageenan coating enriched with essential lemon oil on the quality of rainbow trout (Oncorhynchusmykiss) fillets during refrigerated storage (4 ± 1 °C) over a period of 15 days was evaluated. Trout fillets were analyzed for microbiological (total viable count, Enterobacteriacea counts, lactic acid bacteria, H2S-producing bacteria), chemical (TVB-N, moisture, pH), and biochemical (fatty acids content) characteristics. This study demonstrates the effectiveness of an edible active carrageenan coating in preserving fresh trout fillets from lipid oxidation and microbial growth.